On the rate of convergence of barrier option prices in binomial market to those in continuous time market - Soloveiko, O.; Shevchenko, G. (Інститут математики НАН України, 2008)
We estimate the rate of convergence of barrier option price in a discrete time binomial market to such in a continuous time market.